2000
DOI: 10.1128/jb.182.14.3896-3903.2000
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Defects Caused by Mutations in the isc Gene Cluster in Salmonella enterica Serovar Typhimurium: Implications for Thiamine Synthesis

Abstract: The metabolic consequences of two insertions, iscR1::MudJ and iscA2::MudJ, in the isc gene cluster of Salmonella enterica serovar Typhimurium were studied. Each of these insertions had polar effects and caused a nutritional requirement for the thiazole moiety of thiamine. Data showed that IscS was required for the synthesis of nicotinic acid and the thiazole moiety of thiamine and that one or more additional isc gene products were required for a distinct step in the thiazole biosynthetic pathway. Strains with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 60 publications
7
91
0
Order By: Relevance
“…E. coli strain OD1190, which has a polar disruption of the iscU gene, was a generous gift of Dr. James Imlay. S. enterica strain DM5420 has been described previously (12) and has a polar MudJ insertion in iscA.…”
Section: Strains-mentioning
confidence: 99%
See 2 more Smart Citations
“…E. coli strain OD1190, which has a polar disruption of the iscU gene, was a generous gift of Dr. James Imlay. S. enterica strain DM5420 has been described previously (12) and has a polar MudJ insertion in iscA.…”
Section: Strains-mentioning
confidence: 99%
“…Cell pellets from 3 ml of culture were frozen at Ϫ20°C and assayed within 1 week. Pellets were resuspended and washed in 300 l of 20 mM Tris citrate buffer (pH 8) and assayed as described previously (12).…”
Section: Enzyme Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of metK in plasmid pMETK2 increases AdoMet synthase activity Ͼ5-fold. 2 ThiH* Phenotype Caused by Other Metabolic Functions Is Distinct from That of thiH Alleles-Mutations in loci involved in Fe-S cluster metabolism (gshA, apbC, apbE, iscA) result a ThiH* phenotype (12,18,19). The induction of metK in gshA, apbC, or apbE mutant strain backgrounds failed to allow significant growth in the absence of tyrosine or THZ (data not shown).…”
Section: Effect Of Mutations Affecting the Putative [Fe-s] Clustermentioning
confidence: 96%
“…The characterized proteins of this family generate radical species by reductive cleavage of AdoMet at the [Fe-S] cluster, and structural and biochemical data have shown that the AdoMet molecule binds either the iron that is not liganded by the protein or one of the 3 -bridging sulfides of the cluster (14 -17). Evidence for the presence of an [Fe-S] cluster in ThiH has been provided by genetic (18,19) and biochemical (20) studies. However, data directly tying the [Fe-S] cluster to enzymatic activity have not been reported.…”
mentioning
confidence: 99%